Effects of conjugated polymer on the magnetotransport properties in La0.7Sr0.3MnO3 ferromagnetic electrodes - M. Pesonen; S. Majumdar; H. Huhtinen; P. Paturi; H. S. Majumdar; R. Österbacka (AIP Advances, 2013)
Magnetotransport of La0.7Sr0.3MnO3 (LSMO)/regioregular poly3-hexylthiophene (rr-P3HT) interfaces were studied at 5–300 K to gain insight of spin transport in polymer coated LSMO. LSMO films on SrTiO3 (STO), MgO, and quartz substrates were characterized in pristine state, after depositing rr-P3HT and after removing rr-P3HT. Application and removal of rr-P3HT caused the disappearance of colossal magneto resistance and the emerging of low-field magnetoresistance (LFMR) in STO/LSMO, while the same treatment on MgO and quartz showed only a large LMFR signal with no significant changes during application and removal of rr-P3HT. This result signifies that epitaxial thin films of LSMO do not maintain their transport characteristics when coated with organic semiconductors, posing a limitation for efficient spin polarized injection at such interfaces.